Pendidikan Agama Islam Pada Anak Yang Berhadapan Dengan Hukum di Lapas Klas IIa Curup - Saputra, Febri; Taklimudin, Taklimudin (BELAJEA: Jurnal Pendidikan Islam, 2017)
This research analyzes about Education Islamic on children facing the law in Prisons class IIA Curup. The study is motivated by the importance of Islamic religious education for child prisoners. As already mentioned in UU Number 11 years 2012 on the juvenile justice sytem, that the prison children are entitled to receive education adn training during their stay in prison, as has been done in prisons Klas IIA Curup. Prisons class IIA Curup serve as a source of data because to geta portrait of Islamic religious education, an then can be used as a model for coaching other prison. In this case, islamic religious learning has an important role inthe process of coaching, because one of their awareness is to restore the religion. Inthe process of learning educators provide material that includes the Qurâan, creed, morals shariah worship, but more emphasis on moral material. The methods used in leaarning Islamic religious education in prisons class IIA Curup include; method of guidance based on situation, individual coaching method, group coaching method, suggestion outo ethod, refraction method, advice method, deductive method, lectur method, question and answer method and discussion method. Media used by the blackboard, texbooks and teachers themselves as a demonstrations tool. As for evaluation in learning Islamic religious education prison class IIA Curup is the assessment of tasks and tests given to children.